Holocaust testimony literature: articulating the fine line between fact and fiction - Simões, Anabela Valente
After a reference to Theodor Adorno’s famous and controversial dictum that it would be barbaric to write poetry after Auschwitz, I intend to explore in this essay the circumstance that, particularly during the 90s, many first generation authors tried to come to terms with the past through the process of writing, especially autobiographical novels. Being simultaneously the creator of an artistic rendering and a moral witness of the represented event, the central issue is whether there is a language able to articulate with accuracy the violent personal experiences each subject has endured, or whether it is possible to report such heinous crimes with historical authenticity, in an absolutely mimetic form. The answer to this interrogation lies in the nature of memory itself and the process of recalling experienced or witnessed events: it is inevitable to select events, to adapt them to the subject’s personal perspectives, to interpret what has been lived. There is always a subjective component in the process of recalling the past and, therefore, no individual - despite the fact that the Shoah is an overwhelmingly intense event and ineludible part of the subject’s memory and identity - can record the actual reality; this individual is ‘only’ able to construct a version of that reality, in other words, to fictionalize about his / her experience.